2021
DOI: 10.1371/journal.pone.0247317
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders following electrical injuries—A register-based, matched cohort study

Abstract: Introduction Electrical injuries happen every day in homes and workplaces. Not only may these injuries cause physical damage and disability, they may also cause mental disorders. The aim of this study was to investigate if persons with an electrical injury suffer from mental disorders in the following years. Material and methods In a prospective matched cohort design, we identified 14.112 electrical injuries in two Danish registries and matched these with persons with dislocation/sprain injuries or eye injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A match with 10 match-persons was possible for almost all electrical injuries, before the exclusions. A full flowchart of the study has been published previously in [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A match with 10 match-persons was possible for almost all electrical injuries, before the exclusions. A full flowchart of the study has been published previously in [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only 1/5 of the injuries led to hospitalisation for one day or more (19.4% in DWEA and 21.9% in DNPR). More details on the study population can be found in [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the typical pattern of symptoms occurring immediately after an electrical shock and then receding soon after does not negate the persistence of some symptoms among a small number of victims of electrical injuries. in a recent register-based study that analyzed electrical injuries registered with The Danish National Patient registry (hospital patients) and with The Danish Working Environment Authority (work injuries) over an 18-year period, we found several mental and physical diagnoses related to both mental and physical health 24,48 and to sickleave and low work participation in the subsequent years 32 . In these studies we used a matched cohort design that compared electrical injuries to other injuries, and the participants to other persons with the same occupation.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this match was to take into consideration whether persons in certain occupations were at higher risk of cataract due to socioeconomic factors or other occupational exposure than electric shocks. More detailed descriptions of the matching procedure were reported in an earlier publication (Biering et al, 2020).…”
Section: Match 2: Occupation Matchmentioning
confidence: 99%